Pengaruh Petugas Tidak Resmi terhadap Kinerja Simpang Tak Bersinyal pada Persimpangan Jalan Wahid Hasyim - Jalan Selokan Mataram, Yogyakarta - Romadhona, Prima J.; Hakiki, Moh. Zuhdi Ridwan (Jurnal Teknik Sipil, 2020)
The traffic jam that occurred on Selokan Mataram Street specifically at the intersection of Selokan Mataran Street - Wahid Hasyim Street gave rise unofficial officers or commonly referred to as "Pak Ogah" who took over the police to regulate the traffic. Therefore this research aims to study how the influence of unofficial officers on the performance of the intersection at the Selokan Mataram Street - Wahid Hasyim Street (OB Intersection). The survey was conducted for 2 days which included vehicle volume surveys, vehicle speed surveys, queue length surveys and driving behavior surveys. The results of the VISSIM modeling analysis showed that one-way system management was more effective than unofficial officer with an average delay value of 75.58%. Meanwhile, the length of the queue has decreased and increased. Decrease in the value of the queue length occurred in the north and south by 43.54% and 37.22% and an increase in the west by 31.17%. However, the value of this increase was not as much as the condition of unofficial officers at 78.90% of the existing conditions.